Smart Sensors for Soil Nutrient Analysis in Precision Agriculture (International Journal of Food and Nutritional Sciences, 2022)
Smart sensors have emerged as indispensable tools in precision agriculture, offering real-time data on soil nutrient levels critical for optimizing crop management. This literature-based abstract provides an overview of the role, challenges, and applications of smart sensors for soil nutrient analysis in modern agriculture. Smart sensors employ various technologies, including electrochemical and optical methods, to measure soil nutrient concentrations accurately. They are integrated with data analytics and decision support systems, enabling precise fertilizer management, irrigation scheduling, and pH control. Additionally, these sensors facilitate variable rate fertilization, reducing environmental impact and resource wastage. While smart sensors promise numerous benefits, they face challenges such as accuracy, cost, and data management. Addressing these hurdles requires collaboration among stakeholders and investment in education and training. Furthermore, bridging the digital divide is essential to ensure equitable access to this technology, particularly in developing regions. In conclusion, smart sensors hold the potential to revolutionize agriculture by promoting sustainability, resource efficiency, and responsible farming practices. As technology advances, these sensors are poised to play a pivotal role in achieving global food security and environmental conservation